An optimized handoff scheme for IP mobility support in IEEE 802.11 WLANs - Christos Bouras; Ioanna Sampraku; T Karoubalis (7th ACM International Symposium on Modeling, Analysis and Simulation of Wireless and Mobile Systems (MSWiM 2004), Venice, Italy, 2004)
This paper presents an 802.11-dependent IP mobility solution which ac- celerates the network reconfiguration phase after subnet handoffs and significantly reduces the IP handoff latency. The proposed fast IP hand- off method offers the next generation WLAN applications such as Voice over WLANs (VoWLAN) complete freedom of movement without expe- riencing any connectivity problems. The performance results verify that this method outperforms other existing proposed IP mobility solutions inWLANs, in a way which introduces the lesser imperative amendments to the existing 802.11 wireless LAN framework.